1993
DOI: 10.1177/0887302x9301100309
|View full text |Cite
|
Sign up to set email alerts
|

Fashion Opinion Leadership, Fashion Innovativeness, and Need for Variety

Abstract: The purpose of this study was to identify the relationship between need for variety and four consumer groups: fashion opinion leaders, fashion innovators, innovative communicators, and fashion followers. We predicted that fashion opinion leaders, fashion innovators, and innovative communicators would have a greater need for variety than would fashion followers. Subjects were 425 undergraduate students. Hirschman and Adcock's Measurement of Innovativeness and Opinion Leadership was used to identify the four con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 9 publications
6
86
0
Order By: Relevance
“…This characteristic is similar to that of leaders in fashion (Schrank and Lois Gilmore 1973). Workman and Johnson (1993) suggested that fashion innovators seek variety that can stimulate them and are interested in new clothing styles.…”
Section: The Effects Of Innate Innovativeness On Fashion Leadership Asupporting
confidence: 53%
See 1 more Smart Citation
“…This characteristic is similar to that of leaders in fashion (Schrank and Lois Gilmore 1973). Workman and Johnson (1993) suggested that fashion innovators seek variety that can stimulate them and are interested in new clothing styles.…”
Section: The Effects Of Innate Innovativeness On Fashion Leadership Asupporting
confidence: 53%
“…Sproles (1979) confirmed the role of innovativeness and fashion opinion leadership in the adoption of a new fashion. Workman and Johnson (1993) found positive relationships between fashion opinion leadership and fashion innovativeness. Also, Muzinich et al (2003) postulated individual personality and information seeking behavior as key determinants of fashion innovativeness.…”
Section: The Effects Of Innate Innovativeness On Fashion Leadership Amentioning
confidence: 90%
“…For example, earlier (vs. later) adopters had a greater need for variety (mental stimulation), were higher on sensation seeking and experience seeking, were less susceptible to boredom, and were more innovative [49][50][51][52]. Earlier (vs. later) adopters scored higher on change, risk, and unusual stimuli subscales of the arousal seeking tendency scale [49].…”
Section: Creative Attitudes and Time Of Adoptionmentioning
confidence: 99%
“…Chen et al [53] found that females practiced more pro-environmental behaviors than men. Women reported stronger environmental attitudes, concern, and behaviors than men (e.g., [54][55][56]). Women, then, are more likely to engage in pro-environmental behavior due to cultural and social practices.…”
Section: Pro-environmental Behaviors and Gendermentioning
confidence: 99%